(x+5)(2x-1)=(2x-3)(x+1)

Simple and best practice solution for (x+5)(2x-1)=(2x-3)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)(2x-1)=(2x-3)(x+1) equation:



(x+5)(2x-1)=(2x-3)(x+1)
We move all terms to the left:
(x+5)(2x-1)-((2x-3)(x+1))=0
We multiply parentheses ..
(+2x^2-1x+10x-5)-((2x-3)(x+1))=0
We calculate terms in parentheses: -((2x-3)(x+1)), so:
(2x-3)(x+1)
We multiply parentheses ..
(+2x^2+2x-3x-3)
We get rid of parentheses
2x^2+2x-3x-3
We add all the numbers together, and all the variables
2x^2-1x-3
Back to the equation:
-(2x^2-1x-3)
We get rid of parentheses
2x^2-2x^2-1x+10x+1x-5+3=0
We add all the numbers together, and all the variables
10x-2=0
We move all terms containing x to the left, all other terms to the right
10x=2
x=2/10
x=1/5

See similar equations:

| (3x-1)(x+3)=(2-x)(5-3x) | | 4(3x-2)-3(x-4)=7x+20 | | 13t-10=46 | | 6x+3x=15+21 | | .84=x-27/7 | | F(n+1)=4 | | F(n+1)=1/2 | | 1/20=x/5000 | | -0.2x+x=180-6 | | 3.4x-9.04=8.3 | | 7/21=x/18 | | 7/21=b/18 | | 3(13.7r-1.2)=47 | | 8x-9.02=2.5 | | 3y-13/y+40=23/10 | | 3x-13/x+40=23/10 | | 8/9-3=x | | .03(x)=5 | | 4/9-3=x | | 3/5x-3=1/2x+5 | | x/5=x+3/20 | | -4=-17×x | | 10/10+x=35/56 | | K/3+3k/10=3/2 | | 120+2x=340 | | (3x+8)+(x+12)=360 | | -6b+4+4b=-3b+12 | | 6x+185=8x-207 | | x-7/2=4/3 | | 0=12x^2-24x-16 | | 2(x-3)-4=15-(x+6) | | 2x+(x+1)+(x+35)=180 |

Equations solver categories